1998
DOI: 10.1159/000012257
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Endocrine and Immunological Changes in Psoriasis Patients and Healthy Controls

Abstract: Background: Clinical observations suggest that psychological stress can induce exacerbation of psoriasis. It is hypothesized that these stress effects on the course and outcome of psoriasis are caused by neuroendocrine modulation of immune functions. Therefore we investigated the cardiovascular, endocrine and immunological response to a laboratory stressor in psoriasis patients and healthy controls. Methods: Untreated (n = 7) and PUVA-treated (n = 4) psoriatics and healthy controls (n = 7) were exposed to a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 30 publications
3
65
0
8
Order By: Relevance
“…Interestingly, in a recent study of 50 subjects, it was found that the Arg16 allele frequency was significantly higher in the sporadic psoriasis group as compared to controls [82]. Since increased circulating levels of catecholamines have been observed in psoriatic patients [84], and a 10-fold increase in the expression of the epinephrine sythetic enzyme PNMT is also found in basal keratinocytes in involved psoriatic epidermis [85], it is tempting to propose that long-term exposure to increased levels of catecholamines, in the circulation or locally derived by the keratinocytes themselves, in combination with increased desensitization of beta 2AR in individuals with the Arg16 allele, may predispose to psoriasis.…”
Section: Psoriasismentioning
confidence: 97%
“…Interestingly, in a recent study of 50 subjects, it was found that the Arg16 allele frequency was significantly higher in the sporadic psoriasis group as compared to controls [82]. Since increased circulating levels of catecholamines have been observed in psoriatic patients [84], and a 10-fold increase in the expression of the epinephrine sythetic enzyme PNMT is also found in basal keratinocytes in involved psoriatic epidermis [85], it is tempting to propose that long-term exposure to increased levels of catecholamines, in the circulation or locally derived by the keratinocytes themselves, in combination with increased desensitization of beta 2AR in individuals with the Arg16 allele, may predispose to psoriasis.…”
Section: Psoriasismentioning
confidence: 97%
“…In Graves’ disease, the evidence that ensues is pretty solid, since it is based on independent studies which obtained comparable results by using similar and reliable methods in different countries. Stressful life events may affect the regulatory mechanisms of neuroendocrine-immune functions in a number of ways [32, 33, 34]. Within a multifactorial frame of reference, stressful life events have been consistently associated with several medical disorders.…”
Section: Psychosocial Factors Affecting Individual Vulnerabilitymentioning
confidence: 99%
“…Within a multifactorial frame of reference, stressful life events have been consistently associated with several medical disorders. Table 1 outlines the medical disorders for which controlled studies have pointed to a relationship [11, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40]. …”
Section: Psychosocial Factors Affecting Individual Vulnerabilitymentioning
confidence: 99%
“…A kísérletes vagy valós stresszorokra adott kortizolvá-laszt eddig hat tanulmány vizsgálta, amelyek közül négy alulműködő HPA-tengelyről számolt be [16,54,55,57,60,63]. A bevezetőben említett, a betegségüket saját bevallásuk szerint stresszérzékenynek, illetve a nem stresszérzékenynek tartó pikkelysömörös betegek közöt-ti klinikai különbségek ismeretében érdekes megvizsgál-ni, hogy a két csoport közötti különbség a hormonok szintjén is megjelenik-e. Richards és mtsai azt találták, hogy a betegségüket stresszérzékenynek vallók stresszor előtti bazális kortizolszintjei alacsonyabbak voltak, és a stresszre is csökkent kortizoltermeléssel reagáltak [56].…”
Section: A Hypothalamo-hypophyseo-adrenalis éS a Sympathyco-adrenomedunclassified
“…Schmid-Ott és mtsai [63] A rövidítésjegyzékben nem szereplő rövidítések: TSST = Trier Social Stress Test.…”
Section: Alacsonyabb Kortizolunclassified